Batik Training, an Effort to Increase the Income of Papring Kampoeng Batara Neighborhood Community in Kalipuro District, Banyuwangi Regency - Rahmawati, Rahmawati; Paramita, Ratna Wijayanti Daniar; Nurlaela, Siti; Pujiasmanto, Bambang; Handayani, Sarah Rum; Rudianto, Rudianto; Supriyono, Edy; Arifah, Siti (IMPOWERMENT SOCIETY, 2023)
This community service activity aims to provide knowledge and experience to the Papring Village community regarding innovation and natural coloring of papring batik. This activity was carried out with a counseling/lecture model about batik, design innovation, and the advantages of natural colors in batik. Furthermore, in this activity there was also practice in making batik designs and practice in making color mixtures as well as the coloring process. In this activity, the participants who took part in the activity were Papring Village community members who were members of Papring UMKM in Kampoeng Batara. Some of the universities involved in this activity are UNS Surakarta, ITB Widya Gama Lumajang, UNY, and UNIPI Tangerang. This activity was sponsored by BI Jember. This activity is expected to increase the income and economy of the Papring Village community through innovation in batik design and batik coloring, which makes Papring Batik products of higher quality. Thus, it can increase the sales turnover of Batik Papring and further improve the economy of the Papring Village community.